MEMAHAMI CULTURAL STUDIES: Teori, Ruang lingkup dan Metode - Sholahudin, Umar (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2018)
In the study of critical social science, knowledge produced by humans or society has never been a neutral or objective phenomenon. Human knowledge as a product of culture is always associated with power. In Foucault's language, human knowledge itself contains power. The socio-cultural reality formed by human beings is also inseparable from politics-power. Where there is a relation, there is power. Culture Studies helps us to understand and analyze socio-cultural realities critically. The theoretical point of culture studies is the critical social theory of Marxism. Culture Studies, is a critical social theory that seeks to construct everyday life, which is closely related to contemporary culture, political ideology, class, gender, ethnicity and so on. Culture Studies is a study of cultural reality that uses a multidisciplinary approach and is an interdisciplinary critical theory. Theoretically and practically, Culture studies not only attempt to dismantle the hegemonic-veloatif cultural products, but also build a critical awareness of the emporwering community that is more visible to the community which is egalitarian